Colonização, terra, conflitos e religião: a atuação da congregação dos palotinos no Oeste do Paraná - Silva, Gabriela Thaís Mattia da (2018)
This work addresses the conflictive constitution of the private land ownership expansion process called colonization. In memorialist’s, colonizers’, agents’ and religious institutions’ narratives about the West of Paraná, as long as in colonizing companies’ and part of historiography’s, the conception of colonization starts from a homogenous presupposition, without disputes or even their absence. The purpose of this dissertation is broadening the debate about the relations that permeated colonization and land dispute, involving the Vicente Pallotti Society as one of the colonization process’ dimensions. The Pallottine priests’ performance was approached from their articulation with Pinho e Terras colonizing company and from a land occupation, with judicial confrontation deployment, involving the Vicente Pallotti Society and Sabino Pergentino Delai. As a whole, the study aims to show that the occupation process, which took place in the western region of Paraná, has not occured in a peaceful way. There were several agrarian conflicts. These conflicts were related to each other, directly or indirectly, and were marked by confrontations, among which, those within the judiciary branch.